Water Diplomacy: Perspectives from a Group of Interdisciplinary Graduate Students. (July 2015) - Read, Laura; Garcia, Margaret
Abstract Water management challenges are multifaceted, often involving issues of water availability, quality, access and equity. It is increasingly recognized that professionals trained to work in traditional disciplinary roles are ill‐equipped to address complex issues such as water that transcend both geographic and disciplinary boundaries. A growing number of interdisciplinary doctoral programs, including the Water Diplomacy Integrative Graduate Education and Research Traineeship (IGERT) at Tufts University, have formed to respond to demand for progress in this area. This paper presents a Water Diplomacy IGERT student perspective on the benefits and challenges of interdisciplinary water education. First, we find that articulating a set of shared principles helps to build a strong research community, which in turn shapes the research approach and perspectives of participating students. Second, we recommend students clearly state uncertainties and assumptions to tackle the challenge of working with multidimensional complex systems. Next, we advise that students collaborate with researchers and partner organizations to gain exposure to different approaches outside of their discipline, and to increase breadth of knowledge while maintaining sufficient depth. Finally, we recommend that students take an active role in program leadership to ensure balance between program and student development. These difficulties are not unique to water education, and therefore we hope this discussion can help inform future interdisciplinary education and research efforts.